Body, Oral Discourse and Writing in Augusto Roa Bastos’s Hijo de hombre (Anclajes, 2011)
Augusto Roa Bastos introduces some modifications in the second version of Hijo de Hombre, which exhibit the author’s worries to create a transcultural narrative project, determined by the linguistic duality that characterizes the Paraguayan national territory. In agreement, a series of textual operations and narrative procedures will contribute to embody the impression of oral discourse that guaraní instills into the Spanish writing.
Keywords: writing; orality; body; narration; Roa Bastos